Informal Sector Heterogeneity and Income Inequality : Evidence from the Democratic Republic of Congo - Adoho, Franck M.; Doumbia, Djeneba (World Bank, Washington, DC, 2018)
This paper uses 1-2-3 survey data on the Democratic Republic of Congo to analyze heterogeneity in the informal sector. It empirically identifies three types of entrepreneurs in the sector. The first group of entrepreneurs—top performers -- is growth oriented and enjoys greater access to capital. The second group—constrained gazelles -- includes entrepreneurs who share many characteristics, especially management skills, with the top performers, but operate with less capital. The third group—survivalists—comprises firms struggling to grow. Based on logit and fixed effect ordinary least squares models, the results presented in this paper show that poverty and income inequality are more common among constrained gazelles and survivalists. The paper also shows that income inequality is explained mainly by educational disparities and lack of credit access among entrepreneurs. Additionally, the outcomes of a Blinder-Oaxaca decomposition show that the performance of firms is a key factor in explaining differences in income. Examining the drivers of performance, the paper finds that human capital and managerial skills are important engines of performance.